TRANSFORMASI MANAJEMEN PENDIDIKAN PESANTREN SALAFIYAH DI JAWA TIMUR: STUDI KUALITATIF DI PESANTREN LIRBOYO KEDIRI - Faizin, Mochamad Arif (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
alafiyah in East Java. It was a qualitative research with an etnography method conducted in Pesantren Lirboyo,Ã‚Â Kediri, in 2012. It focused on the transformation of the kyaiÃ¢â‚¬â„¢s leadership, educational methods, and institution.Ã‚Â Pesantren Lirboyo is one of the pesantren salafiyahs in East Java that exists for more than 100 years. It showsÃ‚Â its great ability to survive survive, transform, and grow for a long period of time in which the leadership of theÃ‚Â kyai plays a very significant role. Therefore, this pesantren is worth examining. The article argued that theÃ‚Â transformation from single into dual, collective leadership in the pesantren has been able to reduce conflicts.Ã‚Â The concepts of riÃ¡Â¸ÂÃ„Â, barakah, tawaÃ¡Â¸ÂuÃ¢â‚¬â„¢ and takÃ¡Â¸Âim has been also encouraging the spirits to develop pesantrenbasedÃ‚Â model of educationKeywords: Pesantren, Salafiyah, Transformasi, Manajemen Pendidikan